Racial differences in institutional trust and COVID-19 vaccine hesitancy and refusal - Anisah B. Bagasra; Sara Doan; Christopher T. Allen (BMC, 2021)
Abstract Background Previous research has indicated that demographic differences affect COVID-19 vaccination rates. Trust, in both the vaccine itself and institutional trust, is one possible factor. The present study examines racial differences in institutional trust and vaccine status among a nationally representative sample of adults in the United States. Methods Data for the current study was collected as part of Wave 8 Omnibus 2000 survey conducted by RAND ALP and consisted of 2080 participants. Responses were collected through the online RAND ALP survey in March 2021. Results Trust in the scientific community was the strongest predictor for already receiving at least one dose of the COVID-19 vaccine at the time of study. Asians had a significantly higher trust in the scientific community compared to all other groups. Results also showed a significant difference in level of trust of the government's response to the COVID-19 pandemic with Indian/Alaskan Natives reporting lower trust compared to Whites, Blacks and Asians. Asians also had a significantly higher level of trust when compared to those who identified as racial Other. Those who identify as American Indian/Alaskan Natives had the lowest levels of institutional trust. Trust in the government's response was not indicative of vaccination within the sample. Conclusions Strategies to increase trust of the scientific community can be employed to address vaccine hesitancy through community-based initiatives and building of partnerships between the scientific community and local community stakeholders.